Pengembangan Media Pembelajaran Interaktif Menggunakan Augmented Reality pada Materi Interaksi Manusia dan Komputer Di SMA Negeri 1 Tilamuta - Sabrin K. Djou; Muhammad Rifai Katili; Dian Novian; Arip Mulyanto; Nikmasari Pakaya; Sri Ayu Ashari (Transbahasa, 2026)
This research aims to develop Augmented Reality (AR)-based interactive learning media for human-computer interaction material at the senior high school level. The problem identified at the school indicates that students lack an understanding of processes, input, and output; they know the devices themselves but are unaware of the underlying processes. Therefore, AR media was developed as an alternative that could provide a more interactive learning experience. This research employs the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model and was conducted at SMA Negeri 1 Tilamuta with Class X IPS 1. The AR media was developed using Unity, with validation conducted by media experts and material experts. The results show that the AR learning media falls into the highly valid category, with validation scores of 94% from media experts and 91.76% from material experts. Furthermore, the AR learning media is deemed effective based on improvements in student learning outcomes, with an average pretest score of 51.29% and a posttest score of 79.68%, and an N-Gain value of 0.59, which falls in the medium category. Thus, the developed AR learning media is deemed suitable for use as a learning material for human-computer interaction.